2019
DOI: 10.3389/fimmu.2019.00767
|View full text |Cite
|
Sign up to set email alerts
|

BKV Clearance Time Correlates With Exhaustion State and T-Cell Receptor Repertoire Shape of BKV-Specific T-Cells in Renal Transplant Patients

Abstract: Reactivation of the BK polyomavirus is known to lead to severe complications in kidney transplant patients. The current treatment strategy relies on decreasing the immunosuppression to allow the immune system to clear the virus. Recently, we demonstrated a clear association between the resolution of BKV reactivation and reconstitution of BKV-specific CD4 + T-cells. However, which factors determine the duration of viral infection clearance remains so far unclear. Here we apply a combinati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…For allograft transplant patients, not only the high rate of these comorbidities and frequent contact with medical care, but also—and especially—immunosuppressive therapy can contribute to disease severity. Thus, a crucial role of T cell immunity for the viral clearance and vaccination response has been shown in previous studies 5‐7 . Because of immunosuppression, the quantity and the functionality of antiviral immunity can be impaired, whereas the impact of different immunosuppressive drugs can vary 6 .…”
Section: Discussionmentioning
confidence: 93%
“…For allograft transplant patients, not only the high rate of these comorbidities and frequent contact with medical care, but also—and especially—immunosuppressive therapy can contribute to disease severity. Thus, a crucial role of T cell immunity for the viral clearance and vaccination response has been shown in previous studies 5‐7 . Because of immunosuppression, the quantity and the functionality of antiviral immunity can be impaired, whereas the impact of different immunosuppressive drugs can vary 6 .…”
Section: Discussionmentioning
confidence: 93%
“…The ongoing studies on the factors able to influence the achievement of adequate protection against SARS-CoV-2 infection and its persistence over time represent a hot topic of current research, with the goal of tailoring vaccination and immunotherapy protocols. Patients with impaired renal function commonly show a poorer humoral immune response with a less durable neutralizing function against infections [39,40]. To confirm this view, we evaluated a group of healthcare workers with no comorbidities or renal disease at six months following recovery from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, an increase in BKV-specific T cells directed to BKV proteins (large T- and small t-antigen, and Vp1–3) was shown to predict successful control of BK viremia [ 93 , 96 , 97 ]. Recently, it was found that CD4+ T-cell exhaustion and the diversity of the antigen specific T-cell receptor repertoire affect the BKV clearance time [ 98 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%